DISIPLIN KERJA MEMEDIASI REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN DI ULAAM SUKAJADI - Chyntia Fareira; Hasmawaty AR (Universitas Bina Taruna Gorontalo, 2024)
This research aims to examine the mediating role of work discipline in the relationship between punishment and reward on employee performance. The theoretical framework employed includes justice theory, expectancy theory, and reinforcement theory. The research methodology involves a quantitative approach, and data collection is conducted through the distribution of questionnaires. The study includes a total of 38 respondents, comprising all employees of the Micro Capital Service Unit. The sample size is determined using purposive sampling. Utilizing Likert scales, the questionnaire is disseminated to gather data. Data analysis is carried out using SPSS 22, and the data are subjected to path analysis. The research findings indicate that 1) There is no significant negative influence of reward on performance. 2) There is no significant negative impact of punishment on employee performance. 3) There is a significant positive effect of work discipline on employee performance. 4) Work discipline can serve as a mediator between reward and performance. 5) Work discipline can act as a mediator between punishment and performance.